A GEM for streamlined dynamic CGE analysis: structure, interface, data, and macro application - Cicowiez, Martín (2017)
This paper provides an overview, macro application, and detailed documentation of GEM-Core, a dynamic computable general equilibrium (CGE) model designed for medium- and long-run policy analysis. GEM stands for General Equilibrium Model. GEM-Core can address the issues that typically are relevant for CGE analysis for developing countries, including fiscal space (with its spending, tax, and foreign aid aspects), public investment, social safety nets, trade, jobs, demography, poverty, and inequality. The model is a template model in the sense that, given an appropriately formatted database, applications for different countries can quickly be developed. The data needed for macro applications are very limited, making it possible to apply the model on short notice to virtually any country, including fragile and low-income countries. GEM-Core comes with a user-friendly Excel-based interface through which the analyst may choose between alternative country databases and, for the selected database, do the analysis (define and analyze simulations, including adjustment of selected data and assumptions). The interface lowers entry barriers to CGE modeling and provides a platform around which training may be organized, making it possible to focus courses on economics instead of computer programming.